Effect of dehydration on the inactivation of Listeria monocytogenes and Salmonella enterica on enoki and wood ear mushrooms - Salazar, Joelle K.; Fay, Megan L.; Khouja, Bashayer A.; Chavda, Nirali J.; Patil, Gayatri R.; Ingram, David T. (Frontiers in Microbiology, 2023)
Foodborne illness outbreaks in the U.S. associated with consumption of both fresh and dried specialty mushrooms have recently occurred. Dried wood ear mushrooms were implicated in a salmonellosis outbreak in 2020, while fresh enoki mushrooms were associated with two listeriosis outbreaks in 2020 and 2023. These specialty mushrooms are commercially available in both their fresh and dried states. Due to the short shelf life of mushrooms, dehydration is a common method used in both industry and by consumers to extend the shelf life and preserve quality.Therefore, the aim of this study was to evaluate the use of dehydration on the inactivation kinetics of both L. monocytogenes and S. enterica on enoki and wood ear mushrooms. Fresh mushrooms were inoculated with four strain cocktails of either L. monocytogenes or S. enterica and dried at ambient conditions for 10 min. Following drying of the inoculum, mushrooms were placed into food dehydrators preheated to 70, 80, or 90°C and treated for up to 24 h. At treatment intervals, mushrooms were removed from the dehydrators for pathogen enumeration. Inactivation kinetics for both pathogens were modeled using the Weibull, log-linear with tail, and log-linear with shoulder models. Pathogen reductions of >4 log CFU/g were achieved on both enoki and wood ear mushrooms during dehydration at 90°C after only 2-4 h. At 70 and 80°C, log reductions of >4 log CFU/g were observed on wood ear mushrooms after 4-8 h. On enoki mushrooms, a tailing effect was observed with residual populations (>2 log CFU/g) of L. monocytogenes and S. enterica remaining even after 24 h of treatment at both 70 and 80°C. This study emphasizes the need for an individualized dehydration strategy for each mushroom type to ensure the effectiveness of dehydration as a process to reduce pathogen populations. Results of this study will aid in informing proper time and temperature combinations for dehydration of specialty mushrooms to ensure product safety.